Development of implicit and explicit attentional modulation of the processing of social cues conveyed by faces and bodies in children and adolescents - Oldrati, Viola; Bardoni, Alessandra; Poggi, Geraldina; Urgesi, Cosimo (Frontiers in Psychology, 2023)
Emotions and sex of other people shape the way we interact in social environments. The influence of these dimensions on cognitive processing is recognized as a highly conditional phenomenon. While much of researches on the topic focused on adults, less evidence is available for the pediatric population. This study aimed at examining the development of the modulation of attention control on emotion and sex processing using facial and body expressions in children and adolescents (8-16 years old). In Experiment 1a, participants performed a Flanker task (probing space-based attention) in which they had to indicate either the emotion (happy/fearful) or the sex of the target stimulus while ignoring the distracting stimuli at the side. We found evidence for intrusion of the sex, but not emotion, while younger participants showed a task-relevant influence of sexual features when processing faces, older participants showed such influence when processing bodies. These findings point to a greater attentional modulation exerted by sex, as compared to emotion, during social processing in children and adolescents and suggest a developmental trend of the saliency of facial and bodily cues for the perception of others' sex.